Congenital Melanocytic Nevus and Fibroepithelioma of Pinkus: A Rare Type of Collision Tumor - Bhatta, Anil Kumar; Keyal, Uma; Liu , Yeqiang (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Congenital melanocytic nevus is benign pigmented lesion of the skin usually present at birth. Here we report a case of 61-year-old male who presented with a pigmented lesion on the trunk, which on biopsy showed features of both congenital melanocytic nevus and fibroepithelioma of Pinkus. We reviewed literature for this combination and found only one case reported so far. Hence, it seems that it is very unusual to seefibroepithelioma of Pinkus in conjunction with a melanocytic lesion.